2019
DOI: 10.1017/s0950268819001080
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a training program on the surveillance of Clostridioides difficile infection

Abstract: A high degree of vigilance and appropriate diagnostic methods are required to detect Clostridioides difficile infection (CDI). We studied the effectiveness of a multimodal training program for improving CDI surveillance and prevention. Between 2011 and 2016, this program was made available to healthcare staff of acute care hospitals in Catalonia. The program included an online course, two face-to-face workshops and dissemination of recommendations on prevention and diagnosis. Adherence to the recommendations w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 22 publications
0
11
0
1
Order By: Relevance
“…The incidence of patients diagnosed with a first episode of CDI in our center increased significantly from 0.9 to 5.5 cases per 10,000 patient-days and it is consistent with previous studies [ 4 , 7 , 10 ]. Several factors may explain this increase in the incidence of CDI in addition to the introduction of the more sensitive two-step diagnostic protocol in 2013 [ 7 , 10 , 11 , 13 ]. These factors include an augment in the population at risk and a higher index of clinical suspicion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The incidence of patients diagnosed with a first episode of CDI in our center increased significantly from 0.9 to 5.5 cases per 10,000 patient-days and it is consistent with previous studies [ 4 , 7 , 10 ]. Several factors may explain this increase in the incidence of CDI in addition to the introduction of the more sensitive two-step diagnostic protocol in 2013 [ 7 , 10 , 11 , 13 ]. These factors include an augment in the population at risk and a higher index of clinical suspicion.…”
Section: Discussionmentioning
confidence: 99%
“…A surveillance study in Catalonia showed that the application of a multimodal training strategy that included an online course on CDI, two face-to-face workshops, and dissemination of recommendations on its prevention and the use of an optimal diagnostic algorithm significantly increased the incidence of CDI from 2.20 cases per 10,000 patient-days in 2011 to 3.41 in 2016 [ 11 ]. An optimal diagnostic algorithm comprises a test with high sensitivity as a screening method, such as GDH, followed by a more specific test to detect toxins either by EIA in a first step or by molecular NAAT methods in a second step.…”
Section: Introductionmentioning
confidence: 99%
“…The incidence rate of CDI in Spain has increased from 2.20 cases/10,000 patients in 2011 to 3.41 in 2016 [ 10 ]. C. difficile infections have a high rate of recurrence after the end of treatment, which may complicate the prognosis due to increased morbidity and mortality.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence rate of CDI in Spain has increased from 2.20 cases/10,000 patients in 2011 to 3.41 in 2016 [10]. C. dif- Figure 3 shows the total cost, stratified by subgroups.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation